Cluster analysis of household income and expenditure - Krikštolaitis, Ričardas; Binkauskienė, Gražina (Lietuvos matematikos rinkinys, 2000)
Household income and expenditure under cluster analysis is analyzed. Calculation are made usind data of Lithuanian Department of Statistics, which were collected questioning people at second quarter of 1999 year.